Nurse care management in the family health strategy: integrative review - Marcelo Costa Fernandes; Lucilane Maria Sales da Silva (Universidade Federal do Ceará, 2013)
It is an integrative review, in order to identify the theoretical national production about the nurse care management in Family Health Strategy (FHS), between 2001 and 2011. Data were collected in databases of National Library of Medicine, Latin American Literature and Caribbean Health Sciences and Scientific Electronic Library Online. After the analytical reading of the works, 15 articles were selected for analysis into three thematic categories: Nursing care actions in the FHS; Management practices of nurses in the FHS and Nurse care management within the FHS. The literature was strongly influenced by the traditional model of health care, with ambivalent actions of care and managements, and the gap in knowledge regarding nurse care management in the FHS. It is expected that the nurse care management makes possible the deconstruction and construction of new practices of nurses.